2018
DOI: 10.1007/s12571-018-0842-z
|View full text |Cite
|
Sign up to set email alerts
|

Economic incentives to use fertilizer on maize under differing agro-ecological conditions in Burkina Faso

Abstract: Increasing agricultural productivity while protecting natural resources depends on proper understanding of farmers' incentives to use intensification strategies, including fertilizer. Using a large-scale household dataset collected in rural Burkina Faso, we examined how the response of maize yield to fertilizer, and thus the economic incentives for its use, varied according to agroecological conditions. We employed a Control Function Approach with Correlated Random Effects in order to test and control for endo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 31 publications
3
21
0
Order By: Relevance
“…Munns and Gilliham (2015) reported on the economic constraints associated with soil salinity including reduced profitability. Our data also corroborate other findings of smallholder farmers including an econometric analysis of maize in Burkina Faso (Theriault et al, 2018) and an experimental study in the Mekong Delta (Witt et al, 2006). The latter study suggested that the economic incentives for fertilizer use varied depending on prevailing biophysical circumstances in locations in which farmers grew their crops.…”
Section: Discussionsupporting
confidence: 90%
“…Munns and Gilliham (2015) reported on the economic constraints associated with soil salinity including reduced profitability. Our data also corroborate other findings of smallholder farmers including an econometric analysis of maize in Burkina Faso (Theriault et al, 2018) and an experimental study in the Mekong Delta (Witt et al, 2006). The latter study suggested that the economic incentives for fertilizer use varied depending on prevailing biophysical circumstances in locations in which farmers grew their crops.…”
Section: Discussionsupporting
confidence: 90%
“…In addition to weed timing, we allow the yield response to be conditional on regimes defined by whether soil characteristics are above or below some critical value. The use of threshold modeling to understand soil effects on yield and fertilizer response is increasingly common when combining data from farm surveys and soil laboratories (Burke et al., 2017; 2019; Marenya & Barrett, 2009a; 2009b; Matsumoto & Yamano, 2013; Theriault, Smale, & Haider, 2018). While most previous studies have focused on just one variable and two regimes (e.g., “high” or “low” carbon), we consider two soil variables.…”
Section: Model Specification and Estimationmentioning
confidence: 99%
“…To encourage low-and medium-income rice producers to engage in sustainable farming practices, many of the current agricultural policies will need to be revised. New policies should eliminate any existing subsidies that drive producers to overuse resources [121]. For example, incentives that encourage the use of fertilizers need to be removed [122].…”
Section: Laying the Route To Sustainable Rice Production: What Can Wementioning
confidence: 99%